Hemodynamics in Miners with Severe Mechanical Injury - P. D. Komarov; V. V. Moroz; Yu. A. Churlyaev; L. Yu. Redkokasha; V. Ya. Martynenkov; A. R. Vartanyan; A. V. Makhalin (Общая реаниматология)
Objective: to define the types and specific features of hemodynamic responses in miners with a service length of 10 years or more in the early posttraumatic period after severe mechanical injury.Subjects and methods. Noninvasive central hemody-namic studies using tetrapolar rheography were conducted in 55 injured miners with an underground service length of 10 years or more (a study group) and in 54 victims without underground service (a control group). Major hemodynamic parameters, such as mean blood pressure, heart rate, cardiac index, stroke index, vascular resistance index, were measured over time: on admission and on days 3, 5, and 7. The victims with severe concomitant injury were matched by age and the nature and severity of mechanical injuries.Results. The study has shown that in the early posttraumatic period from days 3 to 7, the miners with an underground service length of 10 years or more had hypodynamic, hyperdynamic, and normodynamic circulations in 37.2, 50.5, and 12.3%, respectively. Unlike the miners, the controls exhibited in this period a hyperdynamic type in 96.0% and only 4.0% were found to have a hypodynamic type.Conclusion. The miners and the victims without underground service were observed to have the similar hemodynamic responses to severe mechanical injuries within the first 24 hours posttraumatically. Beginning with the 3rd-to-7th day, the ratio of hemodynamic circulatory types changed in the miners, by increasing hypodynamic responses. This may be accounted for by the diminished reserve capacities of the circulatory system due to long-term exposure to poor industrial factors.